(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The relevance of the chosen topic is in response to the increasingly clear understanding by the member states of the European Union that digital professional suitability has an important role in increasing the possibilities of adaptation of human capital to the changing requirements of workplaces and the labor market in the conditions of Industry 4.0. The developed system includes tools, selection of criteria and indicators for the assessment of digital skills and competences, necessary for better professional realization and exercise of key professions/positions in modern Bulgarian enterprises, in line with the level of digitization of company processes.